Analisis Pengaruh Pembangunan Berkelanjutan Terhadap PDRB Kabupaten Karimun - Jennifer; Karen (Jurnal Manajemen, Ekonomi, Keuangan dan Akuntansi, 2021)
Gross regional domestic product is used to measure a region’s “standards of living” which explains the importance of having improvement in it but in a sustainable way, the effect of sustainable development affects both directly and indirectly with the GRDP of a region. While there certainly is a correlation between the two, by managing the rates of unemployment and poverty in a region it can make sure the region is developing in a sustainable way, subsequently however there is the effect of both negative and positive from unemployment and poverty rates towards the increasing or decreasing rates of a region’s gross regional domestic product.